Analisis Pengaruh Hifdz Al Maal Terhadap Pengelolaan Harta Pada Pedagang Muslim Pasar Aur Kuning Kota Bukittinggi - Al-Amin Amin; Muhammad Muhammad Taufiq (JESI (Jurnal Ekonomi Syariah Indonesia), 2022)
Maqashid Al-Shari'ah contains five elements, one of which is property (hifdz al-maal). The purpose of this study is to comply with the concept of hifdz al-maal for the management of assets by Muslim traders in Pasar Aur. This research method is quantitative with descriptive analysis and the number of correspondents is 38 Muslim traders. The results of the study show that there is a significant influence on the concept of hifdz al-mala on the management of assets carried out by Muslim traders at the Aur Bukit Tinggi market. The Level of Influence of the hifdz al-maal variable on property management carried out by Muslim traders at the Aur Bukit Tinggi Market greatly impacts the improvement of the economy and people's welfare.